Age and body surface area related normal upper and lower limits of M mode echocardiographic measurements and left ventricular volume and mass from infancy to early adulthood. Issue 3 (September 1994) - Huwez, F U; Houston, A B; Watson, J; McLaughlin, S; Macfarlane, P W
Abstract : BACKGROUND–M Mode echocardiograms can be measured by two different conventions. In addition, normal limits of echocardiographic measurements have customarily been stratified according to age or body surface area. There is therefore a need to develop a more easily managed approach to calculating normal limits of measurements for the two conventions, one of which, the Penn convention, has not previously been used for echocardiographic measurements in children. METHODS–M mode echocardiograms were recorded in 127 healthy subjects aged from 7 months to 19.5 years. Measurements were made from paper recordings according to the recommendations of the American Society of Echocardiographers and those of the Penn convention. RESULTS–Age and body surface area were found to be highly correlated; but for completeness separate age dependent and body surface area dependent equations for the normal limits of M mode echocardiographic variables were developed. CONCLUSION–A set of age dependent equations and a set of body surface area dependent equations are presented for easy calculation of upper and lower limits of normal M mode echocardiographic variables in infants and children.